MANAJEMEN WAKAF PRODUKTIF DAN TANTANGANNYA DI MAJELIS WAKAF DAN KEHARTABENDAAN PDM SURAKARTA - Azhar Alam; Musliah Isnaini Rahmawati; Aditya Nurrahman (Profetika: Jurnal Studi Islam, 2022)
Waqf management is an important part in determining the economic progress of the people, including in a Muhammadiyah community organization. However, research related to waqf in Muhammadiyah is still smallThe purpose of this research is to find out the management of productive waqf in the Muhammadiyah Surakarta City Waqf and Assets Regional Leadership Council and to find out the obstacles experienced by the Surakarta City Muhammadiyah Regional Waqf and Asset Management Council in carrying out productive waqf activities. The research method used is descriptive qualitative. The types of data used are primary and secondary data. Primary data were obtained through interviews with three parties to the Surakarta City Waqf Welfare Council, two waqifs, and four waqf building administrators. The results of this study indicate that the management of productive waqf at the PDM Waqf Property Council of Surakarta City has been running according to the terms and pillars specified. According to Islamic law, the waqf process at the time of the contract for the transfer of waqf property is also carried out, namely by bringing two witnesses, reading the waqf pledge guided by PPAIW. The last stage is the issuance of waqf certificates as property belonging to the association. However, in this study, it was found that the obstacles experienced by the Waqf Wealth Council of PDM Surakarta City were the lack of public understanding of productive waqf so that it could cause waqf activities to run less than optimally. Another obstacle is financial problems because finance has an essential role in carrying out waqf activities. This study can be a reference for waqf institutions to prepare long-term strategies to deal with these obstacles.Pengelolaan wakaf merupakan bagian penting dalam menentukan kemajuan ekonomi umat termasuk dalam sebuah organisasi masyarakat Muhammadiyah. Namun demikian, penelitian terkait wakaf di Muhammadiyah masih berjumlah sedikit. Tujuan dari penlitian ini adalah untuk mengetahui pengelolaan wakaf produktif pada Majelis Wakaf Dan Kehartabendaan Pimpinan Daerah Muhammadiyah Kota Surakarta serta untuk mengetahui kendala yang dialami Majelis Wakaf Dan Kehartabendaan Pimpinan Daerah Muhammadiyah Kota Surakarta dalam melaksanakan kegiatan wakaf produktif. Metode penelitian yang digunakan adalah kualitatif deskriptif. Jenis data yang digunakan adalah data primer dan sekunder. Data primer diperoleh melalui wawancara kepada tiga pihak Majelis Wakaf Kehartabendaan PDM Kota Surakarta, dua orang pewakif, dan empat pengurus bangunan wakaf. Hasil dari penelitian ini menunjukkan bahwa pengelolaan wakaf produktif pada Majelis Wakaf Kehartabendaan PDM Kota Surakarta sudah berjalan sesuai dengan syarat dan rukun yang ditentukan. Proses perwakafan pada saat akad penyerahan harta benda wakaf juga dilakukan sesuai syariat Islam yaitu dengan membawa dua orang saksi, pembacaan ikrar wakaf dipandu oleh pihak PPAIW, kemudian tahap terakhir yaitu penerbitan sertifikat wakaf menjadi harta benda milik persyerikatan. Namun dalam penelitian ini ditemukan kendala yang dialami Majelis Wakaf Kehartabendaan PDM Kota Surakarta yaitu kurangnya pengertian masyarakat mengenai wakaf produktif sehingga dapat menyebabkan kegiatan perwakafan berjalan kurang maksimal. Kendala lainnya yaitu masalah keuangan, karena keuangan memiliki peran penting dalam menjalankan kegiatan perwakafan. Hal tersebut dapat menjadi referensi bagi Lembaga perwakafan untuk mempersiapkan strategi-strategijangka Panjang untuk menghadapi kendala-kendala tersebut.